CAMPOS, Antonia M.; MEDEIROS, Jonas; RIBEIRO, Márcio M.. Escolas de luta. São Paulo: Veneta, 2016 (Coleção Baderna), 352p. - Editor, REA (Revista Espaço Acadêmico, 2016)
CAMPOS, Antonia M.; MEDEIROS, Jonas; RIBEIRO, Márcio M. Escolas de luta São Paulo: Veneta, 2016 (Coleção Baderna), 352p. Curadoria: Jardiel Carvalho